Edukasi penggunaan obat analgesik secara tepat di masyarakat Desa Tuban Kidul - Hanugrah Ardya Crisdian; Berliana Lutfiananda; Agnes Prawistya Sari; Rolando Rahardjoputro; Dheny Rohmatika; Taufik Turahman (Abdimas Siliwangi, 2026)
The self-medication use of analgesics in the community, particularly among housewives, is still frequently carried out without adhering to the principles of rational drug use. This may lead to inappropriate medication use, adverse effects, and other health risks. This community service activity aimed to improve the knowledge and understanding of PKK women in Tuban Kidul Village regarding the proper, safe, and rational use of analgesics. The methods employed included educational counseling, interactive discussions, and the distribution of informational media in the form of leaflets. This activity involved 20 PKK women as respondents. Evaluation was conducted using pre-test and post-test methods to assess changes in participants’ knowledge before and after the intervention. The results showed a significant increase in participants’ knowledge regarding types of analgesics, proper usage, dosage, potential side effects, and the importance of reading medication labels. In addition, participants demonstrated increased awareness of the importance of consulting healthcare professionals before using medications.In conclusion, this activity was effective in improving community understanding of appropriate analgesic use and is expected to promote more rational and responsible medication practices within families and the broader community, particularly in Tuban Kidul Village. Keywords: analgesics, education, rational drug use, community service, PKK women, Tuban Kidul Village